Histatin‐1 is an endogenous ligand of the sigma‐2 receptor. (23rd July 2021) - Son, Kyung‐No; Lee, Hyun; Shah, Dhara; Kalmodia, Sushma; Miller, Ryan Cree; Ali, Marwan; Balasubramaniam, Arun; Cologna, Stephanie M.; Kong, Hyunjoon; Shukla, Deepak; Aakalu, Vinay Kumar
Abstract : The Sigma‐2 receptor (S2R) (a.k.a TMEM97) is an important endoplasmic reticular protein involved in cancer, cholesterol processing, cell migration, and neurodegenerative diseases, including Niemann–Pick Type C. While several S2R pharmacologic agents have been discovered, its recent (2017) cloning has limited biological investigation, and no endogenous ligands of the S2R are known. Histatins are a family of endogenous antimicrobial peptides that have numerous important effects in multiple biological systems, including antifungal, antibacterial, cancer pathogenesis, immunomodulation, and wound healing. Histatin‐1 (Hst1) has important roles in epithelial wound healing and cell migration, and is the primary wound healing agent in saliva. Little is understood about the downstream machinery that underpins the effects of histatins, and no mammalian receptor is known to date. In this study, we show, using biophysical methods and functional assays, that Hst1 is an endogenous ligand for S2R and that S2R is a mammalian receptor for Hst1. Abstract : The Sigma‐2 receptor (S2R) (a.k.a TMEM97) is involved in cancer, cell migration, and neurodegenerative diseases. S2R has been targeted by pharmacologic ligands, but no endogenous ligand is known. The histatin family of endogenous antimicrobial peptides are active in promoting wound healing and epithelial migration in multiple biological systems, but no mammalian receptor is known. Here, we identify histatin‐1 as an endogenous ligand for the S2R.